Protection of EU Economic Interests by Non-Tariff Instruments Importance for Lithuania - Pukelienė, Violeta; Glinskienė, Rasa (Ekonomika, 2000)
The article is about NTB in EU, their classification. There is analysis of NTB which are important for Lithuania today: Public procurement, technical standards, rules of origin and other. The Lithuania business would know them because the consideration NTB has always been difficult. One reason is the creativity of their authors, out also, and more importantly. the lack of data.As tariffs are reduced and the product range of goods being imported evolves, the protection of the Union’s economic interests is shifting more and more towards the use of other instruments. These ‘non-tariff’ measures arc varied and include actions against: unfair competition, restrictions un quantities of imports, counterfeit and pirated goods